Quercetin protects porcine oocytes from in vitro aging by reducing oxidative stress and maintaining the mitochondrial functions - Jiao, Yafei; Wang, Yixian; Jiang, Tiantuan; Wen, Keying; Cong, Peiqing; Chen, Yaosheng; He, Zuyong (Frontiers in Cell and Developmental Biology, 2022)
Quercetin (QUE) is a component of the flavonoid family that shows various therapeutic properties, such as antioxidant effects. However, whether QUE affects porcine oocyte in vitro aging has not yet been investigated. Therefore, in this study, we applied various doses of QUE to freshly isolated porcine oocytes and found that 10 µM QUE improved the oocyte maturation rate in vitro, as reflected by the increased degree of cumulus cell expansion and first polar body extrusion. More importantly, we found that QUE reduced in vitro aging and improved the maturity level of porcine oocytes after another 24 h of culturing, accompanied by the upregulated expression levels of bone morphogenetic protein 15, growth differentiation factor 9, Moloney sarcoma oncogene, and cyclin-dependent kinase 2. In addition, we found that QUE treatment significantly reduced the intracellular reactive oxygen species levels, apoptosis, and autophagy and upregulated the expression levels of superoxide dismutase 2 and catalase in aged porcine oocytes. In addition, QUE restored impaired mitochondrial membrane potential and spindle assembly in aged porcine oocytes. Our findings demonstrate that QUE can protect porcine oocytes from in vitro aging by reducing oxidative stress and maintaining mitochondrial function.